Identificación de patologías que causan decomiso de ganado bovino sacrificado en el centro de faenamiento de la ciudad de Babahoyo. - Tituaña Murillo, Rosa Alba (2025)
This experimental study was carried out at the slaughterhouse in the city of Babahoyo. Its objective was to identify the pathologies that cause the condemnation of cattle and the economic losses they generate for producers. This study was carried out from November 2024 to February 2025. The pathologies present in the different organs of 291 cattle were observed and recorded. The slaughtered cattle were inspected ante-mortem and post-mortem. Complete and partial carcasses were confiscated from 33 bovine organs detected with some alteration or pathology. The most affected organ was the liver, with 28 confiscations representing 85%. The main causes were liver abscesses (61%), cirrhosis (32), and liver flukes (7%). This was followed by the udder with 3 confiscations representing 9%, all due to mastitis. The only heart confiscated, representing 3% of the total confiscations, was due to cardiomyopathy and pericarditis, which in turn caused the organ to become necrotic. There was also a case of bovine hide confiscation due to cutaneous myiasis in different areas, which led to the confiscation of the entire bovine hide, which in turn represented the remaining 3%. In economic terms, the losses were significant: the confiscated livers generated a loss of $907.90 USD (259.4 lb), the udders $44.40 USD (148 lb), the heart $36.60 USD (13.2 lb), and the hide $9.36 USD (78 lb). In total, the economic losses caused by these confiscations were $998.26 USD.